WMU Journal of Maritime Affairs The international Journal for professionals in maritime administration, industry and education - Song, Dong-Wook.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The WMU Journal of Maritime Affairs (JoMA) is an international peer reviewed journal that covers the subject areas of maritime safety, marine environment protection and shipping operations and gives, in this context, special attention to human factors and the impact of technology. JoMA is for scientists and professionals in maritime administration, industry and education. It aims at serving the international maritime community by presenting fresh ideas and current thinking on subjects of topical interest, reporting on relevant research findings and addressing interrelationships between safety, environment protection and efficiency of maritime transport. The journal accepts Articles as well as Book Reviews for publication. Articles in principle should present genuine research findings. However overview articles summarising the status of knowledge in a specific research area may be considered for publication. JoMA considers the inclusion of book reviews if suitable reviews of books relevant to the scope of the journal are available. JoMA has a section dedicated to the activities of the International Association of Maritime Universities (IAMU). The focus of the IAMU section is on Maritime Education and Training (MET). The IAMU section follows a similar editorial review procedure as JoMA and accepts a range of papers for publication: Articles, Issues of Contemporary Interest, Reports and Comments and Book Reviews. Articles and Book Reviews accepted for publication in the IAMU section follow JoMA guidelines. Issues of Contemporary Interest are not always covered by traditional research and valuable lessons can be learnt through reports on best practice or critical discussions from the practitioner$1 (Bs point of view. This is why IAMU encourages experts to express their views on issues of contemporary interest. Reports and Comments can be published to facilitate research activities within the scope of the IAMU section. This allows scientists to voice opinions on published manuscripts and also to stimulate discussions on areas that require further research.s
Keywords: Public international law; Building construction; Environmental law; Environmental policy; Marine sciences; Freshwater; Public International Law; Environmental Law/Policy/Ecojustice.; Marine & Freshwater Sciences; Offshore Engineering